The Death of Slander - Garfield, Leslie Yalof (The Columbia Journal of Law & the Arts, 2012)
Technology killed slander. Slander, the tort of defamation by spoken word, dates back to the ecclesiastical law of the Middle Ages and its determination that damning someone‟s reputation in the village square was worthy of pecuniary damage. Communication in the Twitter Age has torn asunder the traditional notions of person-to-person communication. Text messaging, tweeting and other new channels of personal exchange have led one of our oldest torts to its historic demise. At common law, slander was reserved for defamation by speech; libel was actionable for the printed word. This distinction between libel and slander, however, rests on a historical reality that is no longer accurate. Originally, permanence and breadth of dissemination always coincided. Slander carried only as far as one‟s voice. Because of slander‟s presumed evanescence, common law required plaintiffs to plead special damages—proof of economic harm—in order to recover for slander. The advent of broadcast technology, with its ability to amplify the spoken word, challenged the traditional division of defamation and forced courts and legislatures to reconsider old classifications. Jurisdictions split in their decision to characterize broadcast speech as libel or slander, largely because of divergent views about which aspect of the speech—permanence or breadth of dissemination—was more important. Postbroadcast technology has further complicated the defamation arena, leaving parties unsure of how best to plead their defamation case. In the past decade technology has again changed the way we communicate. The digital communication revolution has created instances of widespread dissemination through quick, nonreflective and often passing statements. This past year, for example, Wael Ghonim‟s tweet to join him in an Egyptian village square lead to the downfall of Egypt‟s political powers. His fleeting comments to those willing to listen caused an entire nation to fall. This Article considers how courts should rule when these tweets, or text messages, not quite printed, not quite spoken, are defamatory. This Article argues that the advent of text messaging, tweeting and other forms of digital communication, which I call “technospeech,” renders the medieval tort of slander irrelevant in today‟s technological world. The article provides new support for the contention that courts and legislatures should treat libel and slander uniformly and should abolish the archaic requirement of proof of special damages, a burden traditionally reserved for the spoken word. Maintaining slander in the Twitter Age, with its requirement of proof of economic harm, vitiates the common law purpose of defamation. Treating all defamation similarly promotes fairness for plaintiffs seeking to rehabilitate their damaged reputation and provides predictability to those bringing defamation claims. A thoughtful and orderly treatment of technospeech mandates that courts and legislatures put the proverbial final nail in the coffin of slander.